Institutional Ownership as a Moderating Variable of Transfer Pricing, Sales Growth, and Earnings Management on Tax Avoidance - Sukowati, Egi Mulia Asa; Sundari, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to test and analyze the presumed factors that influence tax avoidance, namely transfer pricing, sales growth, and earnings management by considering institutional ownership as a moderating variable. The population used in this study are property and real estate companies listed on the IDX 2018-2022. This research uses purposive sampling which considers certain criteria that match the research needs. The data analysis technique of this research was performed using the SEM-PLS method. The findings showed that transfer pricing and earnings management did not contribute to tax avoidance. In contrast, an increase in sales growth can reduce tax avoidance practices. Institutional ownership cannot moderate the influence of transfer pricing, sales growth, and earnings management on tax avoidance.